(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
In this article, we will talk about many countries financing and launching green projects by commercial banks.The methods of financing green projects in the activities of commercial banks include various tools and approaches aimed at supporting environmentally sustainable initiatives. These tools allow banks not only to actively participate in the ecological transformation of the economy but also to act as a catalyst for sustainable development, contributing to reducing the carbon footprint and increasing energy efficiency in various sectors and regions.Key methods include providing green loans and loans, issuing green bonds, investing in green funds and structured financial products, as well as establishing specialized credit lines and programs.